Analisis Bibliometrik Menggunakan VOSViewer: Penerapan Prinsip Syariah Pada PSAK 108 Asuransi Syariah - Suci Rahmadani; Hajjah Aini Makhyarani Nasution; Hafizah Sri Rahma Wulandari; Ewilda Agustina Dongoran; M. Alpansyah Lubis (TIN: Terapan Informatika Nusantara, 2023)
The use of Islamic insurance continues to increase significantly from day to day. Research on sharia insurance continues to grow and is still ongoing. The purpose of this study is to collect the latest data on topics related to Islamic insurance and the latest related research. The method used in this study is the bibliometric method which is an analysis of previous studies on the topic of Islamic insurance by utilizing indexed academic data and based on CrossCef and Google Scholar. Data obtained from publish or perish is then selected which is most appropriate to the topic, then saved. Then this data is processed in the VOSViewer software which visualizes the data in the form of different colored connected lines. It is from this VOSViewer that the results regarding the relevance of the topic of Islamic insurance and previous researchers are obtained. The results show that research topics such as company, indonesia, sharia, sharia’s body, claims, sharia in indonesia indicate keywords that have been widely researched. while topics covered in green such as sharia insurance, sharia insurance company, assets growth, sharia life insurance, study, sampling, research, insurance, premium, investment, and operational cost are topics that have not been widely researched